THE RELATIONSHIP OF ADOLESCENT RESILIENCE WITH SOCIAL SUPPORT TEACHER GUIDANCE AND COUNSELING: HUBUNGAN RESILIENSI REMAJA DENGAN DUKUNGAN SOSIAL GURU BIMBINGAN DAN KONSELING - Syaputra, Miftah Dwi (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2023)
Abstract: Miftah Dwi Syaputra. 16110121.” The Relationship between Adolescent Resilience and Social Support for Guidance and Counseling Teachers”. Thesis. Guidance and Counseling Study Program. Faculty of Science Education. PGRI Semarang University. Dr. Heri Saptadi Ismanto, S.Pd, M.Pd., Kons, Desi Maulia, S.Psi., M.Psi., Psi. August. 2022. Based on the background of the problem, the disciplinary conditions of some students were not good during distance learning. Some students commit violations such as submitting assignments late, not wearing uniforms when online classes, eating and drinking while studying. The research method used is correlational research, because it aims to find out whether there is a relationship between two variables or state the size of the relationship between two research variables. The population in this study were students of class X IPS MAN 1 Demak, totaling 108 students from three classes. The try out will be held in class X IPS 1 with a total of 36 students. The sampling technique used is the Nonpropability Sampling technique. The value of interpersonal communication and self-confidence is obtained from the value of the distribution of the research scale that has been analyzed for validity and reliability. The analysis used to test the validity is product moment correlation and reliability using the alpha formula. The results of the ANOVA analysis in SPSS, if the significant value is > 0.05, then the data distribution is homogeneous and if the significant value is < 0.05, then the data distribution is not homogeneous. With the results of the variable resilience of adolescents and social support of guidance and counseling teachers is homogeneous 0.738> 0.05. The results of the analysis prove that adolescent resilience and social support of guidance and counseling teachers have a significant relationship, then the results of the correlation test are significant, F change 0.01 <0.05, meaning that they have a person correlated in the stage of a strong positive correlation. Suggestions that researchers can convey should improve the resilience of adolescents. Keywords: Adolescent Resilience. Social Support for Guidance and Counseling Teachers